PENERAPAN PIDANA TERHADAP ANGGOTA POLRI YANG MELAKUKAN TINDAK PIDANA PENCURIAN DENGAN KEKERASAN MENGGUNAKAN SENJATA API (Studi Putusan Nomor : 42/Pid.B/2016/PN.Swl dan Putusan Nomor : 43/Pid.B/2016/PN.Swl) - Hendro, Bevi; Faniyah, Iyah; Wibowo, Adhi (UNES Law Review, 2018)
Based on Article 363 paragraph (1) of the 4th Criminal Code, people who commit theft carried out by 2 persons together or more are threatened with a maximum imprisonment of 7 years. Therefore the Case of Crime of Theft with Violence using Firearms based on Decision Number: 42 / Pid.B / 2016 / PN.Swl and Decision Number: 43 / Pid.B / 2016 / PN. 1 (one) year and 10 (ten) months, charge the Defendant to pay a court fee of Rp. 5,000.00 (five thousand rupiah) and pay attention to Article 365 paragraph (2) of the 2nd Book of the Criminal Law. The specification of this research is descriptive analytical. While the approach method used is normative juridical. The data source used is secondary data. The data obtained were analyzed qualitatively and presented descriptively analytically. Based on the results of research and discussion, it can be concluded; First, the application of a criminal against a member of the National Police who commits a crime of theft with violence using firearms in the decision number: 42 / Pid.B / 2016 / PN.Swl and Decision Number: 43 / Pid.B / 2016 / PN.Swl are: Article 365 paragraph (2) of the 2nd Criminal Code, namely: "A maximum sentence of twelve years imprisonment, is imposed, (2nd) if the act is carried out by two people together or more", with the elements of criminal charges of the Prosecutor General, namely: Whose element of goods; Take something; Elements that are entirely or partially owned by others; Elements With the intention to be owned illegally; Elements That are carried out preceded by, accompanied by, or followed by violence or threats of violence, against a person with a view to preparing or facilitating theft, or in the event of being caught red-handed, to allow themselves to escape or other participants, or to retain possession of stolen property; Elements are carried out by 2 (two) people or more together. Secondly, the consideration of the judge in the application of the criminal to a member of the police who committed a crime of theft with violence using firearms in the decision Number: 42 / Pid.B / 2016 / PN.Swl and Decision Number: 43 / Pid.B / 2016 / PN. Swl are: juridical considerations: prosecutor's indictment, witness testimony, defendant's testimony, evidence. considerations that are non-juridical: the background of the defendant and the religion or belief held by the defendant, the physical and spiritual condition of the defendant, as a result of the defendant's actions